Rare diseases: why is a rapid referral to an expert center so important? - Tina Willmen; Lukas Willmen; Anne Pankow; Simon Ronicke; Heinz Gabriel; Annette Doris Wagner (BMC, 2023)
Abstract Background Patients with rare diseases usually go through years of diagnostic odysseys. The large number of rare diseases and the associated lack of expertise pose a major challenge to physicians. There are few physicians dealing with patients with rare diseases and they usually work in a limited number of specialized centers. The aim of this study was to evaluate the diagnostic efficiency of an expert center. Methods The diagnostic pathway of 78 patients of the outpatient clinic for rare inflammatory systemic diseases with renal involvement was analyzed retrospectively. For this purpose, each examination day was documented with the corresponding examinations performed from the onset of initial symptoms. Three time points were considered: The time when patients first visited a physician with symptoms, the time when patients consulted an expert, and the time when they received the correct diagnosis. In addition, it was documented whether the diagnosis could be made without the expert, or only with the help of the expert. The examinations that confirmed the diagnosis were also documented for each patient. Results A correct diagnosis was made without the help of the expert in only 21% of cases. Each patient visited an average of 6 physicians before consulting the expert. Targeted diagnostics enabled the expert to make the correct diagnosis with an average of seven visits, or one inpatient stay. However, referral to the expert took an average of 4 years. Conclusion The data show that rapid and targeted diagnostics were possible in the expert center due to the available expertise and the interdisciplinary exchange. Early diagnosis is of great importance for many patients, as an early and correct therapy can be decisive for the course of the disease.